2021
DOI: 10.3390/cells10020406
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Circulating CD4− CD8− Double-Negative T Cells and Outcomes of Immuno-Checkpoint Inhibitor Therapy—Looking for Biomarkers and Therapeutic Targets in Metastatic Melanoma

Abstract: Background: The role of circulating CD4−/CD8− double-negative T cells (DNTs) in the immune response to melanoma is poorly understood, as are the effects of checkpoint inhibitors on T cell subpopulations. Methods: We performed a basal and longitudinal assessment of circulating immune cells, including DNTs, in metastatic melanoma patients treated with checkpoint blockade in a single-center cohort, and examined the correlations levels of immune cells with clinical features and therapy outcomes. Results: Sixty-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The origin and function of DN T cells in humans is poorly defined, and may include multiple cells with different origins [19]. Further, in humans, DN T cells have been mostly studied in pathological conditions, such as solid tumors (melanoma), transplantation and autoimmune diseases [19][20][21], but little is known about tissue distribution and function in the steady state. Two recent studies described the presence of Mucosal-associated invariant T cells (MAIT) in the endometrium and cervicovaginal tissues, which represents a subset of unconventional DN T cell population with antimicrobial properties [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The origin and function of DN T cells in humans is poorly defined, and may include multiple cells with different origins [19]. Further, in humans, DN T cells have been mostly studied in pathological conditions, such as solid tumors (melanoma), transplantation and autoimmune diseases [19][20][21], but little is known about tissue distribution and function in the steady state. Two recent studies described the presence of Mucosal-associated invariant T cells (MAIT) in the endometrium and cervicovaginal tissues, which represents a subset of unconventional DN T cell population with antimicrobial properties [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the increase in DNT cells in MPE was significantly positively related to LDH, a disease progression marker of lung cancer [22] . The decrease in DNT cells was associated with improvements in melanoma patients [23] . Therefore, we inferred that the increased frequency of DNT cells in MPE may be a sign of tumor exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…The combined therapy of CEACAM1/PD-1 blockade and adoptive DNT cell transfer in lung cancers warrants further research. However, DNT cells in blood were decreased in melanoma patients responsive to checkpoint therapy [23] , suggesting that the fluctuation of DNT cells should be monitored in the combined therapy of CEACAM1/PD-1 blockade against lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since we are proposing DN T-cell expansion as a criterion for solid tumor malignancy, awareness that they may be markedly expanded in some rare blood cancers ( 35) is important to avoid misdiagnosis if solid and blood cancers were to coexist. DN T dominance was also found in cytofluorimetric analyses of tissues from many tumor types such as melanomas, renal cell carcinoma, glioblastoma (36), and melanoma-invaded lymph nodes compared to negative lymph nodes (37). De Tullio et al (38) reported that in Hodgkin's lymphoma, ab-DN Ts were significantly increased as compared with other histotypes, suggesting an important role in the development and progression of Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 90%